Political Imperatives of the Economic Integration of Russia and Belarus: the General Situation and Specifics of the First Quarter of 2021 - V. A. Shamakhov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The economic integration of Russia and Belarus is determined not only by the traditional set of internal factors, but also by the increasing external influence. At the turn of 2020-2021, external factors have become decisive. Under these conditions, the stability of the Belarusian economic model and the nature of foreign economic relations between the two countries became key factors for an effective joint response to external challenges.